EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM AKTIVITAS PAYROLL PADA PT. PAMPERINDO PRIMA - Jordy Christian Hartono; Kurniawan Tjakrawala (Jurnal Paradigma Akuntansi, 2022)
This research aims to analyze the efficiency and effectiveness of the application of accounting information systems in payroll activities at PT. Pamperindo Prima. Type of research used is descriptive qualitative with the object of research is the payroll cycle at PT. Pamperindo Prima. The method in this research is observation, interview and documentation using primary data that comes from sources and company documents. The results of this study indicate that independent commissioners and institutional ownership have a significant influence on firm value, and social responsibility increases influence on firm value. The results of this study indicate that the application of accounting information systems in payroll activities at PT. Pamperindo Prima is still not efficient and effective because it has weaknesses in the organizational structure and company SOPs. The implication of this research is the need to improve the accounting information system in terms of attendance and payroll and changes to company SOPs related to employee work which will increase the efficiency and effectiveness of the existing system.